Spatial anxiety and identity in Toni Morrison’s God Help the Child and Brit Bennett’s The Vanishing Half - Omar, Noritah; Guo, Lifeng (Oxford University Press, 2024)
Homelessness, as disproportionately experienced by Black Americans, is not only the absence of a roofed and walled space but also a visceral feeling of spatial anxiety, unheimlich, and “not-being-at-home.” Even if homelessness is fundamentally a housing problem (Colburn and Aldern 10), this alone does not resolve the psychological sense of homelessness experienced by many minority groups in the United States. Toni Morrison and Brit Bennett interrogate this through Bride in God Help the Child (2015) and Jude in Te Vanishing Half (2020), respectively. Both novels depict the acute sense of homelessness felt by these female protagonists in their homes, a topophilic space, a space of love,ostensibly meant to provide belonging, security, and freedom from fear, revealing how their spatial anxieties transcend physical boundaries and affect their interactions with the outside world. Despite portraying this sense of homelessness, both novels chronicle Black women’s physical and metaphorical journeys to detach themselves from a gendered and racialized geography to achieve a sense of belonging, thus refuting the stereotypical image of Black Americans as inherently disconnected from their communities.